Implementation of Good Corporate Governance and Sharia Bank Performance - Aryati, Aryati (International Journal of Economics (IJEC), 2025)
Bank financial performance is the achievement of activities within a certain period, especially related to the collection, distribution of funds, and other bank operational activities. Good Corporate Governance (GCG) can improve bank performance. One of the important objectives of implementing GCG in Sharia banking is to improve bank performance. A number of important factors are used to measure the implementation of a bank's level, one of whicht is the implementation of GCG.  The level of Islamic banks is an important part of the efforts to increase the trust of shareholders, the public, and customers. The implementation of GCG can help and facilitate Sharia bank management in developing business strategies and making it easier to achieve goals. This study aims to determine the effect of GCG implementation on the level of Islamic banks in Indonesia.  Using the bank's internal respondents. The use of these respondents was expected to provide information related to the implementation of banks. This stud uses a quantitative discrete analysis approach. The research results show that the implementation of GCG has a significant effect on the level of sharia banking. Continuous efforts are needed to implement GCG in the future, especially to increase competitiveness.